Dam related disaster framework for emergency preparedness - Sabri Muda, Rahsidi; Tukiman, Izawati; Mohd. Hussain, Mohd. Ramzi (Malaysian Institute of Planners, 2020)
Continuous approach and solution in solving resilience over a few decades are yet to resolve the main issue in developing sustainable development, disaster risk reduction and new challenges on climate change. Current frameworks that have been developed tend to be over-generalized which required major changes in developing effective frameworks appropriate for specific disaster phenomena. To address this issue, a clear objective and approach are required to help the community, authorities and government to enhance preparedness and response in case of disaster. The main objective of this paper is to present the theory and analysis in the development of effective disaster risk reduction framework for dam related disaster (DRD). With the intention of strengthening societal capacity for resilience, this paper will introduce the framework for disaster preparedness to bridge readiness among community, agency and dam owners. The methodology employed to develop a framework based on ICBDM model conducted in the study area, utilising surveys questionnaire, FGD and hazard assessment. The framework established detailed flow of response throughout all phases including pre-event, during event and post event which include hazard assessment, community and authority planning, establishment of emergency and safe passage, and aims to minimize loss of life and injury. In practice, this framework poses as an interactive and cohesive community approach to face dam related disasters (DRD) which will enhance overall response in disaster risk reduction programs.